Cooperation between neurovascular dysfunction and Aβ in Alzheimer’s disease - Wang, Niya; Yang, Xiang; Zhao, Zhong; Liu, Da; Wang, Xiaoyan; Tang, Hao; Zhong, Chuyu; Chen, Xinzhang; Chen, Wenli; Meng, Qiang (Frontiers in Molecular Neuroscience, 2023)
The amyloid-β (Aβ) hypothesis was once believed to represent the pathogenic process of Alzheimer's disease (AD). However, with the failure of clinical drug development and the increasing understanding of the disease, the Aβ hypothesis has been challenged. Numerous recent investigations have demonstrated that the vascular system plays a significant role in the course of AD, with vascular damage occurring prior to the deposition of Aβ and neurofibrillary tangles (NFTs). The question of how Aβ relates to neurovascular function and which is the trigger for AD has recently come into sharp focus. In this review, we outline the various vascular dysfunctions associated with AD, including changes in vascular hemodynamics, vascular cell function, vascular coverage, and blood-brain barrier (BBB) permeability. We reviewed the most recent findings about the complicated Aβ-neurovascular unit (NVU) interaction and highlighted its vital importance to understanding disease pathophysiology. Vascular defects may lead to Aβ deposition, neurotoxicity, glial cell activation, and metabolic dysfunction; In contrast, Aβ and oxidative stress can aggravate vascular damage, forming a negative feedback loop.